Effect of one-bottle adhesive systems on the fluoride release of a resin-modified glass ionomer Efeito dos sistemas adesivos de frasco único na liberação de flúor de um cimento de ionômero de vidro modificado por resina - Linda Wang; Marília Afonso Rabelo Buzalaf; Maria Teresa Atta (University of São Paulo, 2004)
A dhesive systems associated to resin-modified glass ionomer cements are employed for the achievement of a higher bond strength to dentin. Despite this benefit, other properties should not be damaged. This study aimed at evaluating the short-time fluoride release of a resin-modified glass ionomer cement coated with two one-bottle adhesive systems in a pH cycling system. Four combinations were investigated: G1: Vitremer (V); G2: Vitremer + Primer (VP); G3: Vitremer + Single Bond (VSB) and G4: Vitremer + Prime & Bond 2.1 (VPB). SB is a fluoride-free and PB is a fluoride-containing system. After preparation of the Vitremer specimens, two coats of the selected adhesive system were carefully applied and light-cured. Specimens were immersed in demineralizing solution for 6 hours followed by immersion in remineralizing solution for 18 hours, totalizing the 15-day cycle. All groups released fluoride in a similar pattern, with a greater release in the beginning and decreasing with time. VP showed the greatest fluoride release, followed by V, with no statistical difference. VSB and VPB released less fluoride compared to V and VP, with statistical difference. Regardless the one-bottle adhesive system, application of coating decreased the fluoride release from the resin-modified glass ionomer cements. This suggests that this combination would reduce the beneficial effect of the restorative material to the walls around the restoration. Sistemas adesivos são associados aos cimentos de ionômero de vidro modificados por resina para a obtenção de maior resistência adesiva à dentina. Apesar deste benefício, outras propriedades não devem ser prejudicadas. Este estudo se propôs a avaliar a liberação de flúor a curto prazo de um cimento de ionômero de vidro modificado por resina coberto com dois diferentes sistemas adesivos em um modelo de ciclagem de pH. Quatro associações foram testadas: G1: Vitremer (V); G2: Vitremer + Primer (VP); G3: Vitremer + Single Bond (VSB) and G4: Vitremer + Prime & Bond 2.1 (VPB). SB é um sistema sem flúor e PB contém flúor. Após a confecção das amostras de Vitremer, duas camadas de cada sistema selecionado foram aplicadas e fotopolimerizadas. Em seguida, as amostras foram imersas em solução desmineralizante por 6 horas, seguida da imersão em solução remineralizante por 18 horas, totalizando 15 dias de ciclagem. Todos os grupos liberaram flúor sob o mesmo padrão, apresentando maior liberação inicial e decrescendo ao longo do tempo. VP apresentou a maior liberação de flúor, seguida de V, sem diferença estatística. VSB and VPB liberaram menor quantidade de flúor em relação a V e VP, com diferenças estatisticamente significantes. Independentemente do sistema adesivo de frasco único, houve redução da liberação de flúor pelo cimento de ionômero de vidro modificado por resina. Isto sugere que esta associação poderia reduzir o efeito benéfico do material restaurador em torno da restauração.